S133 A core outcome set for mechanical ventilation trials: the covent study. (15th November 2017) - Ringrow, SM; McAuley, DF; Clarke, M; Marshall, JC; Connolly, B; Rose, L; Blackwood, B
Abstract : There is inconsistency in the selection and measurement of outcomes in clinical trials of mechanically ventilated critically ill patients. 1 This presents challenges when comparing trials, and particularly when undertaking meta-analysis of trial data. A core outcome set (COS) is a minimum set of standardised outcomes that should be reported in every trial of a specific intervention. We therefore aimed to develop a COS for use in future trials where the aim of the intervention is to modify the duration of mechanical ventilation. Mixed consensus methods were used to develop this COS. A large, international, online Delphi study was followed by 2 consensus webinars with representatives from the Delphi panel and additional input from a separate patient representative group teleconference. Participants were recruited via international trials groups, critical care societies, charities and associations. Additional researchers were identified through a PubMed search. Participants represented 4 main stakeholder groups; patients, clinicians, researchers and industry. The study was conducted between December 2015 and October 2016. The Delphi ran over 3 rounds; Round 1 included 24 outcomes obtained from a systematic review. During this round a further 23 outcomes were proposed and added by participants. Numbers of participants completing each round were 200, 178 and 161 respectively. A total of 19 outcomes gained consensus through the Delphi process and were discussed at the consensus webinars and the patient teleconference. The outcomes in the final COS were agreed across all 3 meetings and included mortality, health-related quality of life, duration of mechanical ventilation, reintubation, length of stay and successful extubation (Table 1 ). Using robust consensus methodology this COS has been developed for use in all trials and systematic reviews evaluating interventions that may reduce the duration of mechanical ventilation. Agreement now needs to be reached on how these outcomes should be measured and defined. Reference: Blackwood B, Clarke M, McAuley DF, McGuigan PJ, Marshall JC, Rose L. How outcomes are defined in clinical trials of mechanically ventilated adults and children. American Journal of Respiratory and Critical Care Medicine 2014, Apr 15;189(8):886.